The Influence of Bali Garden-Themed Murals on Visitor Interactivity at Living World Mall Bali - Farhan, Farhan; Anak Agung Gede Rai Remawa; Made Ida Mulyati (Institut Agama Islam Negeri Palopo, 2024)
Murals in the modern era can create interactivity with visitors (users) as a form of participatory description of societal phenomena, particularly murals at Living World Mall Bali (LWMB), which use the Bali garden concept. The aim of this study is to describe interactivity, visitor responses, and the implementation of the Bali garden concept in the murals at LWMB. To achieve these goals, the researcher applies theories and approaches from interactivity, aesthetics, color psychology, and education. The research method is descriptive qualitative, in the form of a case study. Research data include visitor behavior and responses, as well as the construction of murals with the Bali garden concept. Data collection techniques include observation, interviews, and document studies. Data analysis uses an interactive model, consisting of data reduction, data presentation, and verification/conclusion drawing. The research findings contain descriptions of visitor interactivity with the murals, including behaviors such as taking photos, appreciating aesthetic value, using the mural as an inspirational image medium, an information medium, a medium for conveying moral messages, and an educational medium by observing, touching, and documenting. Visitor interactivity with the murals at LWMB serves as a medium for inspiration, a means of conveying moral messages to promote cultural and environmental values of Bali, and an educational medium in the arts, fostering psychological comfort, a sense of brotherhood, and a spirit of mutual cooperation.